Special Requirements For Textile Production On Exporting To The European Market - Nigora Madixanova Saxibdjanovna (Genius Publishing Group, 2022)
This article examines the export of textile products to the European Union with the requirements of international standards.
Keywords: standard; EU; product; requirements